fear of the gods in the literature of ancient Iraq - Abdulwahhab Mohammed, Hiba; Bashar Jumaah, Ahmed (Journal of College of Education, 2022)
ABSTRACT    It is common knowledge in the relationship of humans to Gods that a person looks at his deity with a look filled with fear and dread, as he possesses supernatural qualities that distinguish him from all other creatures, including (strength, courage, boldness, and fearlessness), But in ancient Iraq, the situation is different. The ancient Iraqi man believed in a very large number of gods, and imagined his life as similar to the life of humans in everything, starting from the outward appearance and ending with human emotions and feelings, including a sense of fear.That is, the life and attributes of the gods were like a mirror that reflected the life of man on earth. On the basis of that, the topic (fear of the gods in the literature of ancient Iraq) was chosen, as the research highlights the manifestations of the fear of the gods, trying to shed light on the images of that fear, starting with the motives and ending with the results, relying on a group of literary with indications that the gods have lived a state of fear.
Keywords: fear. Gods. Literature. Ancient. Iraq